ANALISIS EKONOMI KREATIF DAN PENGGUNAAN TEKNOLOGI DIGITAL STUDI TENTANG TRANSFORMASI DAN PELUANG PERTUMBUHAN BISNIS - Suli Da'im; Moh Ali; Dina Novita; Moh Ali Fais; Irwansyah (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to examine the development of the creative economy and the adoption of digital technology through a qualitative approach and bibliometric analysis. Data collection was carried out by reviewing literature published between 2018 and 2023 to ensure the relevance and timeliness of the information. The analysis method used VOSviewer software to identify trends and patterns in the literature and map out research areas that require further exploration. The findings show that, although there is a close connection between the creative economy, technology, and digital economy, the research cluster covering these four topics is relatively smaller compared to other topics, indicating significant research gaps. The study identifies that policies accelerating digital transformation and the development of the creative sector in Indonesia can be key drivers of creative economy growth. Furthermore, digital transformation in Indonesia's economy holds significant potential despite challenges related to technological disparities and labor absorption. This research also highlights the importance of digital infrastructure and the enhancement of human resource quality to support digital economic growth. These findings provide valuable insights for researchers and practitioners to further explore under-discussed topics and offer a strong foundation for future research on the role of the creative economy and technology in creating new opportunities in the digital age.